The Genesis of Private International Law in the Ancient World - Getman-Pavlova Irina (Law Journal of the Higher School of Economics, 2023)
The problems of private international law genesis do not receive some special attention in the Russian doctrine. This situation is regrettable, since a study of history is the basis of the society’s legal culture. The article is aimed at partially filling this gap. It is devoted to the origin of conflicts of different national laws in Ancient Israel and Judea, Ancient Greece, Ancient Egypt. The main attention is paid to the nature of such collisions and the formation of ways to solve them. Attention is drawn to the difference in the nature of conflicts of laws in Israel and Egypt (interpersonal), on the one hand, and in Greece (interpolis), on the other. By writing the study, the author used the methods of comparative analysis and reconstruction, formal-logical, dialectical, natural science and historical methods. The states of the Ancient World were mostly theocratic despotisms characterized by xenophobia and a policy of militant isolationism. However, the objective needs of the economy dictate the need for international trade and recognition of the rights of foreigners. The attitude towards foreigners evolves from their complete lack of rights to the provision of national treatment to them, and this takes place in all states. In local courts, foreign personal law is recognized and applied, which makes it possible to assert the formation the connecting factor “lex personalis”. For foreigners, special courts are created, which in the process take into account the language of the contract, the origin of the parties and the place of conclusion of the contract. The main source of rules for choice of law is jurisprudence in all states; interpolis agreements play an important role in ancient Greece; the necessary regulation is derived through the interpretation of the Torah in Ancient Israel; conflict norms are fixed in the royal edict in Hellenistic Egypt. In conclusion, it is concluded that the PIL of the Ancient World is a collection of individual cases, this is “episodic private international law”. The limited amount of data does not allow drawing general theoretical conclusions, building a general line of evolution of the rules for applicable law. However, it is precisely the ancient and biblical approaches will subsequently become the intellectual foundation for the creation of scientific doctrines of PIL and its legislative regulation.